Rethinking women's leadership development: Voices from the Trenches - Robin Selzer; Amy Howton; Felicia Wallace (Administrative Sciences, 2017)
As recent graduates of a women's-only leadership development program in higher education in the United States, we used autoethnography as a research methodology to provide critical insight into effective women's leadership programming and evaluation. The potential of this methodology as both a learning process and product helped elucidate two key findings: (1) to effectively develop women leaders, work must be done at the personal, interpersonal, and organizational levels, as these levels are interrelated and interdependent; and (2) women's multiple identities must be engaged. Therefore, relationship-building should be a central learning outcome and facilitated through program curricula, pedagogical methods, and evaluation. Including autoethnography as a program evaluation methodology fills a gap in the literature on leadership development, and supports our goal of making meaning of our personal experiences in order to enhance women's leadership development.
Keywords: 350; women's leadership; leadership program evaluation; gender equity; intersectionality; identity; higher education; career advancement